Cervical vertebral and dental maturity in Turkish subjects - Başaran, Güvenç; Ozer, Törün; Hamamci, Nihal (American journal of orthodontics and dentofacial orthopedics, 2007)
Introduction: The aim of this study was to investigate the relationships between the stages of calcification of teeth and the cervical vertebral maturity stages in Turkish subjects. Methods: A retrospective cross-sectional study was designed. The final study population consisted of 590 Turkish subjects. Statistical analysis of the data was performed with computer software. Spearman rank order correlation coefficients were used to assess the relationship between cervical vertebral and dental maturation. For a better understanding of the relationship between cervical vertebral maturation indexes and dental age, percentage distributions of the studied teeth were also calculated. Results: Strict correlations were found between dental and cervical vertebral maturation of Turkish subjects. For males, the sequence from lowest to the highest was third molar, central incisor, canine, first premolar, second premolar, first molar, and second molar. For females, the sequence from lowest to the highest was third molar, canine, second premolar, first premolar, central incisor, first molar, and second molar. Conclusions: Dental maturation stages can be used as a reliable indicator of facial growth.